2016
DOI: 10.3109/09637486.2016.1170770
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of antioxidants in Japanese parsley

Abstract: Two cultivars of Japanese parsley were harvested in different seasons; their antioxidant capacities were evaluated by oxygen radical absorbance capacity (ORAC) methods, and the contents of hydrophilic and lipophilic antioxidants were compared. Japanese parsley possessed potent antioxidant capacities both in hydrophilic and lipophilic extracts when evaluated by ORAC methods. LC/MS/MS analyses revealed that chlorogenic acid and four kinds of quercetin glycosides were major antioxidants in the hydrophilic extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Parsley did not show significant differences with red cabbage in the ORAC assay, and showed the highest antioxidant capacity in the FRAP and DPPH methods. Antioxidant capacity values obtained for parsley were similar to those reported by Stratil et al (), but other authors have reported lower values (Karaca & Velioglu, ; Ogita et al, ; Stratil et al, ; Tiveron et al, ), which suggest that the parsley sample under study presented a greater antioxidant capacity than the average of the same vegetable.…”
Section: Resultssupporting
confidence: 85%
“…Parsley did not show significant differences with red cabbage in the ORAC assay, and showed the highest antioxidant capacity in the FRAP and DPPH methods. Antioxidant capacity values obtained for parsley were similar to those reported by Stratil et al (), but other authors have reported lower values (Karaca & Velioglu, ; Ogita et al, ; Stratil et al, ; Tiveron et al, ), which suggest that the parsley sample under study presented a greater antioxidant capacity than the average of the same vegetable.…”
Section: Resultssupporting
confidence: 85%
“…Analysed using HPLC, chlorogenic acid (227 mg/g) is the dominant phenolic compound in the ethanol extract of O. javanica 11 . The hydrophilic extract contains chlorogenic acid, quercetin rhamnosyl galactoside, rutin, hyperoside and isoquercitrin, while lutein, γ-tocopherol and α-tocopherol have been identified in the lipophilic extract 12 . Major chemical constituents of the essential oil from O. javanica are incensole (26%), α-copaene (18%) and n-nonylacetate (18%) 13 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…10 It is likely that differences in the environmental conditions (eg, climate, location, and soil fertility) of the collected foods and the measurement methods employed are the reasons for these differences. 33,34 We found that seasonings and spices, especially seasonings with soybean products, such as miso made high contributions to AOC. Previous studies reported extremely high H-and L-ORAC values for certain spices and herbs, indicating that the component essential oils contained considerable quantities of antioxidants.…”
Section: Discussionmentioning
confidence: 88%